Teachers’ Views: Using Body Music in Teaching and Learning Primary School Subjects - Muzaffer Özgü Bulut; Ayşe Akarsu; Ersoy Karabay (Center for Educational Policy Studies Journal, 2025)
The paper presents research conducted among Turkish primary school classroom teachers regarding their personal and professional views about creating and using KeKeÇa body music games as educational tools. The core principles of the KeKeÇa body music approach – embodiment, play orientation and arts integration – are increasingly recognised as important topics in education today. The research is a phenomenological study with ten young women, primary school teachers who teach at village schools in the mountains. The teachers went through the KeKeÇa training programme, which aims to enable participants to make use of body music in teaching primary school curriculum content. They designed and used body music games for all classroom subjects, especially those that were more difficult to learn in the first place. In order to investigate the teachers’ views, data were collected using an open-ended questionnaire and analysed using MAXQDA software. The results show that the teachers gained more control of the lessons, which became much more fun. They reported improvement in students’ motivation and joy, adding that the learning showed greater long-term retention and became less time consuming. In conclusion, according to the participant teachers, the KeKeÇa body music approach, attitude and practice made remarkable contributions to their professional skills and had a beneficial effect in teaching and learning diverse subjects, and an enriching impact on their students’ motivation, joy and learning quality.